The effect of a 6-week plyometric training on explosive power in volleyball players - Jastrzebski, Z.; Wnorowski, K.; Mikolajewski, R.; Jaskulska, E.; Radziminski, L. (Baltic Journal of Health and Physical Activity, 2014)
Background: The purpose of the present study was to determine the effects of a six-week plyometric high and low-intensity training on the explosive power of lower limbs in volleyball players. Material/Methods: The research was conducted on a sample of 30 volunteers of the Sports Club at Gdansk University of Technology in Gdansk. Before the experiment, the players were divided into two homogeneous groups. After two weeks of an introductory common stage, each group followed a plyometric regime of different intensity. The results showed that the high-intensity program was more efficient than the low-intensity program in developing the explosive power in the volleyball players. Results: The largest significant improvement was observed for the vertical jump with arm swing (11% in HIJG and 3.8% in LISG). The strongest correlations were registered for the maximal power and the total mechanical work obtained in the Wingate test (r=0.83), and the power of jumps during attacks and blocks (r=0.78). Conclusions: The experiment confirmed high effectiveness of the training loads applied in the experiment, in particular in the high-intensity program.